2009
DOI: 10.1007/s00221-009-1880-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in quantifying multisensory integration: alternative criteria, models, and inverse effectiveness

Abstract: Single neuron studies provide one foundation for understanding many facets of multisensory integration. These studies have used a variety of criteria for identifying and quantifying multisensory integration. While a number of techniques have been used, there lacks an explicit discussion of the assumptions, criteria, and analytical methods traditionally used to define the principles of multisensory integration. This was not problematic when the field was small, but with rapid growth a number of alternative tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
163
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 75 publications
(101 reference statements)
11
163
1
2
Order By: Relevance
“…These suppressive interactions cannot easily be explained by saturation or other nonlinearities in the BOLD response (Buxton et al, 2004), but rather suggest sublinear neural mechanisms of audiovisual integration and are consistent with previous fMRI results of object categorization and speech recognition in which only subadditive interactions at the level of the BOLD response were observed (Werner and Noppeney, 2010a,b;Lee and Noppeney, 2011). In the putamen and sensory areas, the operational mode of multisensory integration depended on the reliability or effectiveness of the sensory motion information, as expected under the classical principle of inverse effectiveness (Meredith and Stein, 1983;Stein and Meredith, 1993;Stanford and Stein, 2007;Stein and Stanford, 2008). Therefore, even though the interactions were always subadditive, they turned from response suppression for intact stimuli into a significant response enhancement for degraded stimuli.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These suppressive interactions cannot easily be explained by saturation or other nonlinearities in the BOLD response (Buxton et al, 2004), but rather suggest sublinear neural mechanisms of audiovisual integration and are consistent with previous fMRI results of object categorization and speech recognition in which only subadditive interactions at the level of the BOLD response were observed (Werner and Noppeney, 2010a,b;Lee and Noppeney, 2011). In the putamen and sensory areas, the operational mode of multisensory integration depended on the reliability or effectiveness of the sensory motion information, as expected under the classical principle of inverse effectiveness (Meredith and Stein, 1983;Stein and Meredith, 1993;Stanford and Stein, 2007;Stein and Stanford, 2008). Therefore, even though the interactions were always subadditive, they turned from response suppression for intact stimuli into a significant response enhancement for degraded stimuli.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, our study revealed subadditive integration profiles concurrently in both auditory and visual areas in the absence of parietal activations, suggesting integration mechanisms at the level of sensory motion processing. Indeed, recent studies have accumulated evidence for low-level multisensory integration in putatively unisensory areas (Schroeder and Foxe, 2002;van Atteveldt et al, 2004;Macaluso and Driver, 2005;Murray et al, 2005;Schroeder and Foxe, 2005;Bonath et al, 2007;Kayser et al, 2007;Lakatos et al, 2007;Lewis and Noppeney, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear effect of multisensory integration, i.e., cross-modal stimuli resulting in stronger responses than either auditory or visual stimuli alone (subadditive enhancement) (Stein et al, 2009), was found for the theta response only. This finding is in line with other studies that found effects of multisensory integration within the theta frequency band (e.g., Sakowitz et al, 2005).…”
Section: Multisensory Effectsmentioning
confidence: 91%
“…There has been much discussion however around the pros and cons of the statistical criteria used to classify multisensory integration when comparing bimodal to unimodal conditions using fMRI (Beauchamp, 2005;Calvert, 2001;Goebel and van Atteveldt, 2009;Laurienti et al, 2005;Stein et al, 2009). The three main criteria used in fMRI research are: 1) the super-additive criteria, which requires the bimodal response to be greater than the sum of both unimodal responses; 2) the max criteria that requires the bimodal response to be greater than the largest unimodal response and; 3) the mean criteria requiring the bimodal response to be greater than the mean of the unimodal responses.…”
Section: Introductionmentioning
confidence: 99%